Adipokines in patients with hypertensive disease with obesity in the dynamics of combined antihypertensive therapy - P. G. Kravchun; O. I. Kadykova; U. S. Herasymchuk (Regulatory Mechanisms in Biosystems, 2021)
Hypertensive disease today is one of the most common cardiovascular diseases, as well as the most common disease associated with obesity. Evaluation of the level of adipokines, namely adiponutrin and galanin, depending on the degree and duration of hypertension, the degree of obesity and their correction against the background of combined antihypertensive therapy is relevant for further understanding of this comorbidity and improvement of the early diagnostics. 127 people were examined, including 107 patients with hypertension of degree 1–3 and 20 healthy persons. Of the patients included in the study, the adiponutrin and the galanin levels were determined in 58 patients, out of which 22 were prescribed different regimens of combined antihypertensive therapy. To determine the level of adiponutrin and galanin, an enzyme-linked immunosorbent assay was used. A significant increase was found in the blood serum of the examined adipokines in comparison with the control group: the galanin level was 4.8 times higher than in the control group, the adiponutrin level in patients with this comorbid pathology was 3.3 times higher than that in the control group. The galanin level is most pronounced in patients with hypertension of degree 3 and obesity of degree 3, which is confirmed by the presence of a direct correlation with systolic, diastolic and pulse blood pressure, very low density lipoprotein cholesterol. The adiponutrin level in the blood serum increased correspondingly to the increase in body mass index: in patients with obesity of degree 3 it was 15.8 times higher than this indicator in patients with normal body weight, 8.8 times higher than in patients with overweight, 6.1 times higher than in patients with obesity of degree 1 and 2.5 times higher than in patients with obesity of degree 2. The levels of the studied adipokines in patients differed also relative to the duration of hypertension. There was a 1.8-, 5.1-, 5.2-fold increase (respectively, ≤5, 6–10, >10 years) of the galanin content in the blood serum compared to the control group. Also an increase of the serum adiponutrin level was noted in comparison with the control group. Against the background of combined antihypertensive therapy, we observed favourable dynamics of galanin and adiponutrin. It is important to conduct further studies to assess the activity of galanin and adiponutrin with a longer follow-up period in wider populations.